The Effect Of Diorama Learning Media On Student Learning Outcomes In Pkn Class IV - Bthalia Margaretha Siburian; Sukardo Sitohang; Osco Parmonangan Sijabat (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the effect of diorama learning media on student learning outcomes in Civics Lessons for Fourth Graders at the UPTD of Public Elementary School 125549 Pematangsiantar. This study used a quantitative research method with a